To the evaluation of raw materials of medical plants of Ulytau mountains (Karagandy region) - Ишмуратова, М.Ю.; Матвеев, А.Н.; Ивлев, В.И.; Мырзалы, Г.Ж. (Fundamental and Experimental Biology, 2015)
At the territory of Ulytau mountains to the base of investigations were determined the spreading and raw ma-terials of 10 species if medical plants. By ability of using of medical plants of Ulytau mountains as sources of raw materials we separated all species to the following categories: species having the wide area, forming the significant natural square and suitable to industrial gathering; species having small natural area and suitable for gathering of raw materials for necessities of the local medicine network; species sprouting as individual exemplars and not forming natural squares which are suitable to gathering of raw materials; species having safe status, that is to say rare, disappearing, endemic plants.